(untitled) (Iraqi Journal of Medical Sciences, 2024)
Background: The Corona virus disease 2019 (COVID-19) is a complicated respiratory syndrome caused by novel Corona virus that spread swiftly throughout the world. Objective: To study correlation between IgG spike protein-1 and soluble inhibitory immune checkpoints and among checkpoints in individuals vaccinated with booster dose of BNT162B2 vaccine. Methods: This research is cross-sectional, performed on 180 healthy adults (above 18 years old) vaccinated with BNT162B2 vaccine, 21-30 days after booster dose at community dwelling from December 2021 to April 2022. Measuring serum level of IgG toward spike protein-1 and soluble negative regulatory markers by enzyme-linked Immunosorbent assay. Results: This study showed a significant negative correlation between IgG titer and soluble inhibitory immune checkpoints, soluble CTLA-4 (r = -0.23, P value = 0.001), soluble PD-1 (r = -0.12, P value = 0.04) and soluble PD-L1 (r = -0.204, P value = 0.006), while Inhibitory immune checkpoints had a positive significant correlation among them (p value